2015
DOI: 10.1039/c5cc03951g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic meta-selective C–H functionalization to construct quaternary carbon centres

Abstract: A catalytic meta-selective C-H functionalization of 2-phenylpyridines using a range of tertiary halides is described. The protocol is simple to perform and uses commercially available reagents to construct challenging quaternary carbon centres in a regioselective manner. Preliminary studies suggest the C-H functionalization proceeds through a radical process directed via a remote σ-activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(65 citation statements)
references
References 36 publications
2
61
0
2
Order By: Relevance
“…14,15,16 In order to investigate a possible the SEAr pathway, the effect of various sulfonating reagents were subjected to study ( Table 2). Interestingly, it has recently been demonstrated that similar ruthenium complexes such as [Ru( t BuCN)6][BF4]2 can catalyse the C-H arylation of fluoroarenes and arenes with directing groups.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…14,15,16 In order to investigate a possible the SEAr pathway, the effect of various sulfonating reagents were subjected to study ( Table 2). Interestingly, it has recently been demonstrated that similar ruthenium complexes such as [Ru( t BuCN)6][BF4]2 can catalyse the C-H arylation of fluoroarenes and arenes with directing groups.…”
Section: Figurementioning
confidence: 99%
“…Once the metallacycle is formed the introduction of a functional group can be achieved at the ortho 1,2 and meta positions. Recently, new examples of meta selective catalytic C-H functionalization controlled by the catalyst have been achieved Scheme 1 using secondary 14 or tertiary 15,16 alkyl halides and bromination reagents. 1,2 Despite the great achievements in this area, the direct introduction of a functional group at the meta position remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Yu and co-workers also reported a meta-selective alkylation of a-aryl acetamides by cooperative palladium and norbornene catalysis to introduce primary alkyl chains. [4] Yu and co-workers also reported a meta-selective alkylation of a-aryl acetamides by cooperative palladium and norbornene catalysis to introduce primary alkyl chains.…”
mentioning
confidence: 99%